2013
DOI: 10.1109/tasc.2013.2241812
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mechanical Properties of Tubular Materials With Hydraulic Bulge Test for Superconducting Radio Frequency (SRF) Cavities

Abstract: The plastic constitutive equation of tubular materials under hydraulic pressure needs to be determined for the successful application of hydroforming technique to the seamless fabrication of multicell superconducting radiofrequency cavities. This paper provides the empirical constitutive properties of tubular material determined by tensile and hydraulic bulge tests. During an experimental bulge test, the internal pressure, bulge height and wall thickness were continuously measured. Based on this data, the flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The results of the study emphasized the importance of bulge testing, at the time, rather than tensile testing when deriving the constitutional relationships eventually needed for continuum modeling the hydroforming of SRF cavities. We subsequently went on to include the material's anisotropic properties and used an anisotropy coefficient to determine the flow stress curve of anisotropic materials [10]. It was demonstrated that a more accurate flow stress curve can be obtained by considering anisotropic properties.…”
Section: Evolution Of the Modelling Approachmentioning
confidence: 99%
“…The results of the study emphasized the importance of bulge testing, at the time, rather than tensile testing when deriving the constitutional relationships eventually needed for continuum modeling the hydroforming of SRF cavities. We subsequently went on to include the material's anisotropic properties and used an anisotropy coefficient to determine the flow stress curve of anisotropic materials [10]. It was demonstrated that a more accurate flow stress curve can be obtained by considering anisotropic properties.…”
Section: Evolution Of the Modelling Approachmentioning
confidence: 99%
“…The above equations 2.1 and 2.2 lay the foundation to calculate the circumferential and longitudinal stress components and fit the flow stress curve, which are first derived by Woo et al [50] and then used in many studies [23,56,66,[88][89][90][91][92][93]. Fuchizawa et al [53] improve this stress model by taking into account the wall thickness of metal tubes, and following re-searchers [54,55,58,59,63,71,72,81,87,[94][95][96][97][98][99][100] recommend this new formula because it is more in line with the actual situation.…”
Section: Analytical Modelmentioning
confidence: 99%